Pharmacological validation of the anxiolytic, muscle relaxant and sedative like activities of Capsicum annuum in animal model (Bangladesh Journal of Pharmacology, 2017)
The current study deals with anxiolytic, muscle relaxant and sedative like activities of Capsicum annuum in animal models. The crude extract was found safe in acute behavior and toxicity studies. However, the n-hexane fraction caused severe acute toxicity. Pretreatment of crude extract and n-hexane fraction elicited marked dose-dependent antianxiety-like effects in elevated plus-maze and dark and light models. The results showed significant (p< 0.05) antianxiety-like effects of crude extract while highly significant (p< 0.001) for n-hexane fraction. Similarly, an effect on muscle coordination was tested in traction model, where both crude extract and n-hexane fraction evoked marked dose-dependent activity. The effect of thiopental-induced sleep test of crude extract and n-hexane fraction was highly significant (p< 0.001). All together, the results revealed potent anxiolytic, muscle relaxant and sedative like activities of C. annuum in animal models and the pharmaco-logically active constituents are mostly non-polar in nature.Video Clip of Methodology:4 min 31 sec:   Click to watch